SAINT SERGEY OF RADONEZH'S SPIRITUAL HERITAGE AND DESTINIES OF RUSSIA - K. M. Dolgov (MGIMO University Press, 2014)
The article is devoted to the memory of Reverend Sergius of Radonezh whose 700th anniversary Russia is celebrating this year. It reviews the heritage of Reverend Sergius of Radonezh in Russian history, the meaning of his name for the Russians, the spiritual and political role of the Christian Orthodoxy in history. The spiritual heritage of Reverend Sergius of Radonezh survived his life and eventually turned into bottomless source of moral authority for the Russian people. His name is a constant reminder of the moral resurrection of the Russian people after ages of feudal strives and Tatars' yoke, which paved the ground for the consequent political rise of Russia. It proves the rule that political power rests on moral authority. The memory of Reverend Sergius of Radonezh is a good benchmark, which we can always check ourselves against, whether we are living up to it or failed. In any case it will remain the guiding light for Russia.